Enhancing comparability of sustainability reporting : selection of core indicators for company reporting on the contribution towards the attainment of the Sustainable Development Goals : executive summary (UN New YorkUS, 2017)
Suggests some issues for discussion, with a view to building consensus around the proposed list of core indicators, thereby contributing to greater comparability of sustainability reporting and consistency with financial reporting frameworks.
Keywords: SUSTAINABLE DEVELOPMENT